BARKAMOL ShAXS TARBIYaSIDA SAN’AT VA PEDAGOGIKA UYG’UNLIGI - Mustafayev, Sh.N. (SCIENCE and SOCIETY, 2021)
Art has a great influence on the development of the individual and society, helps a person see the world, enriches his inner world, spirituality, and the development of intelligence. Spirituality, which embodied art and pedagogy, was a means of enlightenment and upbringing. There is a common, social genesis in art and pedagogy.
Keywords: art pedagogy; genesis; alla; culture; art; classics; mentality; improvisation; music; singing; vocal art